Communication Skills: The Difference between Role Playing and Direct Learning Models for Social Artimatics - Pangestika, Suci Kusrianti Indri (Journal Evaluation in Education (JEE), 2022)
Research objectives: This study aims to determine the differences in the results of mathematical communication skills between students who were treated with the role playing learning model and students who were treated with the direct learning model.Methodology: This type of research is descriptive quantitative. The sample studied was 64 students, consisting of 32 students in the experimental class (VII E) and 32 students in the control class (VII D). Analysis of the data used to determine the differences in the results of learning communication using the t test.Main findings: The results of this study were first carried out by calculating the n-gain, namely the calculation of the increase in the average pretest and posttest in both classes and the experimental class n-gain was 0.71 and the control class n-gain was 0.61, then the experimental class and control class calculation of mathematical communication skills in the form of writing obtained tcount > ttable that is 5,4266 > 1,6699. So that the average mathematical communication ability of students by learning the role playing model is higher than the mathematical communication ability of students with direct learning. This shows that there is a difference between students' mathematical communication skills in writing in the experimental class and the control class.The novelty of the research: The novelty of this research is to examine how students communicate mathematically in written form.